2006
DOI: 10.1097/01.phm.0000179442.59847.27
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Upper and Lower Limb Casting and Orthoses in Children with Cerebral Palsy

Abstract: The objective of this overview is to summarize from systematic reviews the evidence on the effectiveness of using upper and lower limb casting or orthoses in children with cerebral palsy. We used computerized bibliographic databases to search for systematic reviews without any language restrictions. Identification, selection, quality assessment, and data extraction were performed independently by two investigators. Of the 40 identified reviews, 23 were selected for closer consideration, and five reviews met th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 34 publications
1
39
0
2
Order By: Relevance
“…Treatments will aim to address the concerns and priorities identified by families at the initial screening visit, typically the reduction of impairments and symptom management to ease pain and discomfort. Therapy regimes will be based on international consensus recommendations [19,61,62] and will include practices such as: serial casting to lengthen muscles and reduce contractures, [45,63-66] strengthening of injected muscles and antagonists, [67] provision of stretching programs to be implemented into the child’s daily routines, [68] provision of splints/orthoses, [69] and/or targeted motor training. It is recognized that children with non-ambulant CP will have difficulties participating in movement based therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Treatments will aim to address the concerns and priorities identified by families at the initial screening visit, typically the reduction of impairments and symptom management to ease pain and discomfort. Therapy regimes will be based on international consensus recommendations [19,61,62] and will include practices such as: serial casting to lengthen muscles and reduce contractures, [45,63-66] strengthening of injected muscles and antagonists, [67] provision of stretching programs to be implemented into the child’s daily routines, [68] provision of splints/orthoses, [69] and/or targeted motor training. It is recognized that children with non-ambulant CP will have difficulties participating in movement based therapy.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is important to determine what effect this improvement in quality of movement has on their ability to function in their everyday lives, as conflicting results have been reported in other studies 3,8,12,13 . The findings also emphasised that there is little evidence for the continued effect achieved by splinting, and that it has been found that once splinting is removed, the benefits ceased 7 .…”
mentioning
confidence: 87%
“…The findings also emphasised that there is little evidence for the continued effect achieved by splinting, and that it has been found that once splinting is removed, the benefits ceased 7 . Splinting material and regular monitoring of the correct fit and condition of the splint -if required for a long period of time -can be a costly intervention 12 . Therefore, the achievement of outcomes in the long term through the use of splinting must be weighed up against the cost of this intervention method used over an extended period 7 .…”
mentioning
confidence: 99%
“…Ayr›ca pozisyonlama ve anormal kas tonusunun düzenlenmesinde son y›llarda bas›nç splintlerinin ve 1950'li y›llardan bu yana da anormal kas tonusunun düzenlenmesinde, postüral düzgünlü¤ün sa¤lanmas›nda, istemli kontrolün ö¤renme yolu ile sa¤lanmas›nda kullan›lan elektromyografik (EMG) biofeedback e¤itiminin etkinli¤i de vurgulanm›flt›r. Tüm bu yöntemlerin hemiplejik SP'li çocuklar›n rehabilitasyonunun yan› s›ra duyu, alg› ve iletiflim problemlerinin çözümünde de etkinli¤i oldukça önemlidir (8,(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: G Gi Ir Ri Ifl Flunclassified